A Flexible, Self‐Floating Composite for Efficient Water Evaporation. Issue 6 (4th November 2018) - Fang, Zhenxing; Jiao, Shihui; Wang, Boran; Yin, Wen; Pang, Guangsheng
Abstract: A flexible, self‐floating W18 O49 /carbon foam composite is fabricated by calcining melamine foam with W18 O49 as an adsorbate in N2 atmosphere. This self‐floating property is simply realized by a carbonization process other than the complicated surface modification process. The simple synthesis procedure helps to increase not only the solar absorption but also the retention of W18 O49 in the porous net structure. This composite absorbs almost the whole solar spectrum and generates localized heat at the surface, which is beneficial for water evaporation. Its water evaporation rate is 6.6 times higher than that of pure water. It has a stable cyclic performance over ten cycles under the illumination of simulated sunlight (500 W Xe lamp). Its flexibility makes it easy to reuse and transfer, which is evaluated by the bending deformation test. The W18 O49 /carbon foam composite is a prospective material in solar energy conversion field, and the preparation procedure is feasible to scale‐up. Abstract : A flexible, self‐floating composite is fabricated by calcination of melamine foam with W18 O49 under N2 atmosphere, and this composite could efficiently improve water evaporation under simulated sunlight. Its bending deformation test also shows good flexibility, which is essential for practical application.